1990
DOI: 10.1007/bf01724795
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of human growth hormone stimulated by human growth hormone releasing factor following severe cranio-cerebral trauma

Abstract: Patients suffering from severe cranio-cerebral trauma show alterations of the secretory patterns of thyroid stimulating hormone (TSH) and human growth hormone (HGH) which may be of prognostic significance. We studied 10 patients following severe brain injury and prospectively compared a new synthetic human growth hormone releasing factor (HGHRF) test with the thyrotropin releasing hormone (TRH) test. On admission, all patients had a Glasgow Coma Scale score of 3 or 4. All patients had a low T3 syndrome. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…In this regard, only a few authors have evaluated the relationship between outcome from TBI and the presence of pituitary dysfunction. As mentioned above, either positive or negative relationships between pituitary dysfunction and outcome from TBI have been observed in the early, acute phase post-TBI (41,46,47,61). We did not find any statistical correlation between outcome measures and presence of pituitary dysfunction, both in patients examined over a 5-year period after TBI (5) and in patients evaluated during the early rehabilitation period (48).…”
Section: Consequences and Treatment Of Pthpmentioning
confidence: 49%
See 1 more Smart Citation
“…In this regard, only a few authors have evaluated the relationship between outcome from TBI and the presence of pituitary dysfunction. As mentioned above, either positive or negative relationships between pituitary dysfunction and outcome from TBI have been observed in the early, acute phase post-TBI (41,46,47,61). We did not find any statistical correlation between outcome measures and presence of pituitary dysfunction, both in patients examined over a 5-year period after TBI (5) and in patients evaluated during the early rehabilitation period (48).…”
Section: Consequences and Treatment Of Pthpmentioning
confidence: 49%
“…A blunted GH response to arginine (ARG) stimulation has been found in patients with severe TBI and very poor outcome (41). Gottardis et al (46) reported that a GH-releasing hormone (GHRH) test elicited a significant (43). These data indicate an imbalance of the complex neuroendocrine system controlling GH secretion during the acute phase post-TBI, but they do not draw reliable conclusions.…”
Section: Consequences Of Tbimentioning
confidence: 99%
“…As mentioned above, either positive or negative relationships between pituitary dysfunction and outcome from TBI have been observed in the early, acute phase post-TBI. (39,40,41,42) We did not find any statistical correlation between outcome measures and presence of pituitary dysfunction, both in patients examined over a 5-years period after TBI (5) and in patients evaluated during the early rehabilitation period. (43) Autopsy studies demonstrated a high incidence (14-74%) of anatomical lesions in the hypothalamic-pituitary region; this suggests, therefore, that hypopituitarism might contribute to the poor prognosis of the TBI patients.…”
Section: Consequencesmentioning
confidence: 61%
“…A blunted GH response to GHRH administration has been found to be associated with increased mortality (Gottardis et al, 1990).…”
Section: Acute Changes In Pituitary Function After Tbimentioning
confidence: 99%
“…TSH responses to thyroid-releasing hormone (TRH) are variable (Eledrisi et al, 2001). An absent TSH response to TRH has been shown to be associated with high mortality (Gottardis et al, 1990).…”
Section: Acute Changes In Pituitary Function After Tbimentioning
confidence: 99%